Diagnostic gaps in vulvar diseases from referral to final diagnosis in a specialized center: analysis of pathways and recommendations for enhancing future diagnostic accuracy - Cornelia Betschart; Tharani Thillainathan; Vera Berger; Isabel Kolm; Brigitte Leeners (BMC Women's Health)
Abstract Background Vulvar diseases have a serious impact on women’s quality of life and can be challenging to diagnose. Correct diagnosis is, however, mandatory for appropriate treatment. Therefore, the aim of this study was to evaluate diagnostic quality regarding the classification of disease symptoms, the suspected diagnosis of referring doctors, the agreement of suspected diagnosis with final diagnosis and the latencies from onset of symptoms to final diagnosis, thereby identifying potential resources for improvement. Methods Retrospective data from the electronic medical charts of 325 patients attending the interdisciplinary vulva clinic at the University Hospital Zurich between January 2016 and December 2020 were analyzed. The consistency between suspected diagnosis at referral and the definitive diagnosis was investigated against the background of vulvar pathology, disease symptoms, specialization of the referring physicians involved, diagnostic steps and time until diagnosis. Results Referral diagnoses were inconsistent with final diagnoses in 96 (43.8%) cases. The time between symptom onset and final diagnosis ranged from 15.9 ± 10.6 to 71.1 ± 92.9 months, depending on the vulvar pathology. In cases of dysplasia, eczema, lichen sclerosus and lichen planus, diagnosis at referral and final diagnosis matched best, while other inflammatory diseases, vulvodynia, and chronic infectious diseases (bacterial/fungal/viral) represented the greatest diagnostic challenges. Suspected diagnosis from gynecologists matched in 36.1% of cases, compared to 83.3% for dermatologists. No standardized pattern for the use of any specific diagnostic technique by referring physicians could be identified. Conclusion There is significant diagnostic latency and variability in accuracy across vulvar disorders and referring specialists. A systematic diagnostic approach, including symptom evaluation, clinical inspection and appropriate diagnostic testing, is lacking. Standardized methods for symptom documentation, clinical assessment, diagnostic testing, and collaboration with specialized vulvar centers are essential to streamline the precision and efficiency of diagnosis as a basis for optimized treatment strategies. Trial registration BASEC 2019 − 00976.